2019
DOI: 10.3390/w11071377
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Combined Aerobic–Anoxic and Methane Oxidation Bioreactor System Using Mixed Methanotrophs and Biogas for Wastewater Denitrification

Abstract: We developed a lab-scale aerobic–methane oxidation bioreactor (MOB)–anoxic system, combining a MOB and the aerobic–anoxic denitrification process, and evaluated its potential for advanced nitrogen treatment in wastewater treatment plants (WWTPs). The MOB used biogas generated from a WWTP and secondary-treated wastewater to support mixed methanotroph cultures, which mediated the simultaneous direct denitrification by methanotrophs and methanol production necessary for denitrifying bacteria in the anoxic chamber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Furthermore, the nitrogen and phosphorus contents in the methanotroph sludge showed that the TN content in the activated sludge of the wastewater treatment plant was 5.34% on average, but was 8.53% in the methane-oxidizing bacteria sludge. This result suggests that methanotroph growth has a high nitrogen demand [35].…”
Section: Denitrification Characteristics Of Digested Fw Leachatementioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the nitrogen and phosphorus contents in the methanotroph sludge showed that the TN content in the activated sludge of the wastewater treatment plant was 5.34% on average, but was 8.53% in the methane-oxidizing bacteria sludge. This result suggests that methanotroph growth has a high nitrogen demand [35].…”
Section: Denitrification Characteristics Of Digested Fw Leachatementioning
confidence: 89%
“…Furthermore, in the metabolism process of methanotrophs, ammonia was oxidized to N 2 O through NH 3 OH in the same path as that of the ammonia oxidation of ammonia-oxidizing bacteria (AOB) by the methane monooxygenase (MMO), which is a methane-oxidizing enzyme [34,35]. Consequently, the tendency of removing high concentration ammonium and some nitrates in the digested FW leachate by using methanotrophs and biogas was verified.…”
Section: Denitrification Characteristics Of Digested Fw Leachatementioning
confidence: 99%
“…Results of this study illustrated the critical role of pH in CO 2 capture. In future studies on slag filter-upgraded septic tanks, the analysis could be extended to methane release, an important greenhouse gas [29], as methanogenesis could be affected by the pH rise induced by the slag filter, considering an optimum anaerobic digestion pH range of 6.5 to 7.5 [30]. Methanogenesis inhibition by a high pH was achieved in microbial electrolysis cells [31].…”
Section: Carbon Dioxide Flux Into the Septic Tankmentioning
confidence: 99%
“…Results of this study illustrated the critical role of pH in CO2 capture. In future studies on slag filter upgraded septic tanks, the analysis could be extended to methane release, an important greenhouse gas [27], as methanogenesis could be affected by the pH rise induced by the slag filter, considering an optimum anaerobic digestion pH range of 6.5 to 7.5 [28]. As methane produced from small septic tanks is released to the atmosphere, the use of slag filters could reduce greenhouse gas emission by reducing methanogenesis in the septic tank.…”
Section: Carbon Dioxide Flux Into the Septic Tankmentioning
confidence: 99%